The accuracy of prognostic scoring systems for post-operative morbidity and mortality in patients with perforated peptic ulcer - Nichakankitti, Noppawan; Athigakunagorn, Jadsada (International Surgery Journal, 2016)
Background: To determine the accuracy of Boey score, American society of anesthesiologists (ASA) score, peptic ulcer perforation (PULP) score and the mannheim peritonitis index (MPI) score and compare each predicted scoring systems for prediction the morbidity and mortality of patients with perforated peptic ulcer. Methods: We retrospectively reviewed the patients with gastric or duodenal ulcer perforation in Bhumibol Adulyadej Hospital, Bangkok, Thailand between 1 January 2008 and 31 December 2012. The morbidity and mortality within 30 days of the PPU patient who underwent the surgical procedure was determined. The predicted scoring systems included Boey score, ASA score, PULP score and MPI score were calculated. We used area under curve of receiver operating characteristics curve to compare the scoring accuracy. Results: The study included 140 patients, Female 17.9% and male 82.1%. The mean age was 48.5 years. The most common site of PPU was the pre-pyloric region (80%). The most common operative procedure was the simple suture with omental graft. The complication rate was 20.71%. Overall mortality rate was 3.57%. The AUC for morbidity prediction was 0.671 for Boey score, 0.684 for ASA score, 0.698 for MPI score and 0.727 for PULP score. The AUC for mortality prediction was 0.728 for Boey score, 0.776 for ASA score, 0.771 for MPI score and 0.784 for PULP score. Conclusions: The PULP score may be the better prognostic scoring system for post-operative morbidity and mortality of PPU patient than Boey score, ASA and MPI.